End of life in high-security prisons in Switzerland: overlapping and blurring of “care” and “custody” as institutional logics - Marti, Irene (Journal of correctional health care, 2017)
Similar to other institutions, the Swiss prison system faces a growing number of elderly prisoners, trends toward securitization, and, in consequence, more prisoners who will spend the end-of-life (EOL) period of time in prison. By law, prisoners should have the same access to care as the rest of the population. However, custody makes meeting the demands of medical and palliative care difficult. This article focuses on the organizational challenges related to EOL care. Based on ethnographic and documentary research, it examines the institutional logic of the prison and the competing “new” logic emerging with EOL care. It illustrates the ambivalences within these logics and the blurred distinction between “care” and “custody” and evaluates how prison staff interpret this overlap and the effects in shaping everyday practices.